Application of Bilingual Classroom Learning to English Language Skills at SD Muhammadiyah 1 Gempol Elementary School Students - Friza Brillianty Shabrina; Muhlasin Amrullah (International Consortium of Education and Culture Research Studies, 2021)
This study aims to determine the history of the bilingual class and the application of bilingual class learning at SD Muhammadiyah 1 Gempol. The research process uses data collection methods with interviews and observations. The subject of this research is the Principal of SD Muhammadiyah 1 Gempol. The focus in this research is how the history or the beginning of the bilingual class and how the implementation of bilingual class learning. Based on the results of the research, the bilingual class at SD Muhammadiyah 1 Gempol is a class that uses 2 languages in its delivery, namely Indonesian and English which were initiated by the principal at the SD and as a different brand than other schools in the Gempol area. The application of bilingual classroom learning uses 3 additional lessons using books with Cambridge Curriculum Singapore. Read, write, and count selections are made for students who will enter the bilingual class. There is a change in the requirements for bilingual classes that are carried out so that their implementation can be carried out properly.